Laparoscopic uterosacral ligament suspension: a systematic review and meta-analysis of safety and durability - Ronsini, Carlo; Pasanisi, Francesca; Cianci, Stefano; Vastarella, Maria Giovanna; Pennacchio, Marika; Torella, Marco; Ercoli, Alfredo; Colacurci, Nicola (Frontiers in Surgery, 2023)
• Introduction: Pelvic Organ Prolapse (POP) is a widespread condition affecting from 40 to 60% of women. Reconstructive vaginal surgeries are the most commonly performed. Among those, uterosacral ligament suspension (USLS), usually performed transvaginally, preserves pelvic statics and dynamics and seems to be an effective method. Laparoscopic USLS is a valid alternative to vaginal approach and the aim of our review is to confirm its safety and feasibility and to compare clinical outcomes among the procedures. • Methods: Following the recommendations in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, we systematically searched the Pubmed and Scopus databases in December 2022. We made no restriction on the publication year nor on the country. Data about POP-Q recurrence rate (RR), intraoperative and postoperative complications (graded according to Clavien Dindo Classification), readmission rate (RaR) and reoperation rate (RoR) were collected and analysed. We used comparative studies for meta-analysis. • Results: 9 studies fulfilled inclusion criteria. 2 articles were non-comparative retrospective observational studies; 3 more articles were comparative studies where laparoscopic USLS was confronted with other surgical techniques (only data of Laparoscopic USLS were analyzed) and 4 were comparative retrospective cohort studies between laparoscopic and vaginal USLS procedures. The comparative studies were enrolled in meta-analysis. Patients were analyzed concerning perioperative risks and risk of recurrence. Meta-analysis highlighted no clear inferiority of one technique over the other. • Discussion: Laparoscopic USLS is a technique with a low complication rate and low recurrence rate. Indeed, the use of laparoscopy allows better identification of anatomical landmarks and access to retroperitoneum, Moreover, efficacy over time and durability of LPS USLS was also observed. However, these data should be weighed in light of the length of Follow-Up, which was in a very short range. Further, focused and prospective studies will be needed to confirm this finding.